2019
DOI: 10.1248/cpb.c19-00157
|View full text |Cite
|
Sign up to set email alerts
|

Development of Metal Nanoparticle Catalysis toward Drug Discovery

Abstract: Transition-metal nanoparticles (NPs) catalysts supported on solid material represent one of the most important subjects in organic synthesis due to their reliable carbon-carbon or carbon-heteroatom bondforming cross-coupling reactions. Therefore methodologically and conceptually novel immobilization methods for nonprecious transition-metal NPs are currently required for the development of organic, inorganic, green, materials, and medicinal chemistry. We discovered a self-assembled Au-supported Pd NPs catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 96 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…The small size of NPs also allows them to penetrate cell membranes, making them highly reactive. Metal NPs are already being used for biomedical applications [ 16 , 17 , 18 ]. Although it has been shown that gold, silver, and platinum metal NPs exhibit antiparasitic activity [ 19 , 20 , 21 , 22 ], these are precious metals and are expensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small size of NPs also allows them to penetrate cell membranes, making them highly reactive. Metal NPs are already being used for biomedical applications [ 16 , 17 , 18 ]. Although it has been shown that gold, silver, and platinum metal NPs exhibit antiparasitic activity [ 19 , 20 , 21 , 22 ], these are precious metals and are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The small size of NPs also allows them to penetrate cell membranes, making them highly reactive. Metal NPs are already being used for biomedical applications [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This is because single-crystal X-ray analysis reveals atomic coordinates with high precision. Recently, X-ray absorption near-edge structure (XANES) spectroscopy 7,8) has been applied to the analysis of non-covalent conventional hydrogen bonds and halogen bonds of APIs. 9,10) In X-ray absorption spectroscopy, X-ray absorbances increase sharply when the X-ray energy is high enough to excite electrons in the core orbitals, such as the K-shells.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra shapes at the edges and up to around 50 eV above the edges are called X-ray absorption near edge structures (XANES), and their shapes are unique depending on the electronic states of the X-ray absorbing atoms. 2,3) Weak interatomic interactions in API crystals, such as hydrogen bonds and halogen bonds, were shown to perturb the XANES shape by affecting the electronic states of the X-ray absorbing atoms. This means that XANES spectroscopy can be used to identify the crystal forms of APIs.…”
Section: Introductionmentioning
confidence: 99%